Engineering the Production of Major Catechins by Escherichia coli Carrying Metabolite Genes of Camellia sinensis - Kabir Mustapha Umar; S. M. Abdulkarim; Son Radu; Azizah Abdul Hamid; Nazamid Saari (The Scientific World Journal)
A mimicked biosynthetic pathway of catechin metabolite genes from C. sinensis, consisting of flavanone 3 hydroxylase (F3H), dihydroflavonol reductase (DFR), and leucoanthocyanidin reductase (LCR), was designed and arranged in two sets of constructs: (a) single promoter in front of F3H and ribosome-binding sequences both in front of DFR and LCR; (b) three different promoters with each in the front of the three genes and ribosome-binding sequences at appropriate positions. Recombinant E. coli BL (DE3) harbouring the constructs were cultivated for 65 h at 26°C in M9 medium consisting of 40 g/L glucose, 1 mM IPTG, and 3 mM eriodictyol. Compounds produced were extracted in ethyl acetate in alkaline conditions after 1 h at room temperature and identified by HPLC. Two of the four major catechins, namely, (−)-epicatechin (0.01 ) and (−)-epicatechin gallate (0.36 mg/L), and two other types ((+)-catechin hydrate (0.13 mg/L) and (−)-catechin gallate (0.04 mg/L)) were successfully produced.